(untitled) (Research, Society and Development, 2021)
Objective: To unveil the feelings aroused at the time of diagnosis to the labor reintegration process of nursing workers contaminated by Covid-19. Methods: Qualitative, descriptive study, which used as methodological reference the Discourse of the Collective Subject (DSC) and as theoretical reference the Theory of Social Representations. Data collection was done through semi-structured audio-recorded interviews addressing the participants about their feelings during the diagnosis of Covid-19; damage caused by Covid-19 in their health and support networks that helped them to return to work activities. Fourteen health professionals from a reference hospital for Covid-19 care were interviewed. Results: Regarding gender, 85.7% of the interviewees were female and the median age in years was 36 years old approximately. Of these professionals 76.6% declared themselves white and 21.4% brown. Of the interviewed professionals, 50% are nurses and 50% are nursing technicians. 28.6% of the nurses had a graduate degree. The DCS are permeated by feelings of fear, anxiety, hope and insecurity. All these feelings are related from the moment of diagnosis to the return to work activities. During the return to work activities the professionals report damages such as reduced memorization that impact the professional practice. Final Considerations: Feelings of exhaustion, anxiety, fear, insecurity, among others, permeated the return to work activities and the professional trajectory during the global pandemic condition; the responses to these feelings can reflect directly on the practice and mental health of nursing professionals.